Mitigating Genetic Erosion in Cocoa and Coffee: Drivers, Impacts, and Sustainable Conservation Solutions in African Agroecosystems - Babatunde, Olaitan Paul; Odey, Chinyere Florence; Sulaimon, Feyisetan Omolola; Balogun, Shamsudeen Tomiwa; Ojetola, Mary Ayobami; Eshiozemagbon, James Oluwasegun; Tijani, Abdul-Akeem Abiodun (Eurasian Journal of Applied Biotechnology, 2025)
Genetic erosion in tropical cash crops such as cocoa and coffee threatens global food security and the livelihoods of millions of farmers. This study analyses deforestation, germplasm collections, and conservation efforts from 2001 to 2023 in eight African nations. The findings reveal significant deforestation in cocoa-producing regions such as Côte d’Ivoire and the Democratic Republic of Congo and losses in coffee areas such as Ethiopia, which affect genetic diversity. Genebanks rely heavily on cultivated varieties, risking allele depletion. Coffee is more prone to erosion due to forest loss, while monoculture practices threaten cocoa. The study calls for better conservation, increased in situ and ex situ efforts, and sustainable agroforestry. Global cooperation is crucial to maintaining the resilience of cocoa and coffee to climate and economic challenges.